2005
DOI: 10.4269/ajtmh.2005.73.140
|View full text |Cite
|
Sign up to set email alerts
|

Case-Control Study of Mosquito Nets Against Malaria in the Amazon Region of Colombia

Abstract: The degree of effectiveness of mosquito nets against malaria in the Americas has remained uncertain. We carried out a case-control study of net use and mild malaria in the Amazonas state of Colombia. Two hundred ninety cases were enrolled via the Health Department services, and 977 community-based controls matched for age, sex, and place of residence. We found that a large proportion of the population (96% of controls) slept under nets. Nevertheless, we found a benefit of impregnated nets compared with no net … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 25 publications
2
35
0
7
Order By: Relevance
“…Consistent with the third hypothesis, two studies have provided evidence that insecticide-treated bed-nets are effective for malaria control in Amazonia. The first was a case-control study in Colombia that showed more than 50% reduction in malaria, relative to no net use, although the advantage of impregnated over non-impregnated nets was not statistically significant [56]. The second study, a randomized trial of lambdacyhalothrin- versus placebo-treated nets in the Amazonas State of Venezuela, showed a protective efficacy of 55% [57].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the third hypothesis, two studies have provided evidence that insecticide-treated bed-nets are effective for malaria control in Amazonia. The first was a case-control study in Colombia that showed more than 50% reduction in malaria, relative to no net use, although the advantage of impregnated over non-impregnated nets was not statistically significant [56]. The second study, a randomized trial of lambdacyhalothrin- versus placebo-treated nets in the Amazonas State of Venezuela, showed a protective efficacy of 55% [57].…”
Section: Discussionmentioning
confidence: 99%
“…Así mismo, en la región amazónica de Colombia se encontró que el uso del toldillo disminuye el riesgo de infección por malaria en un 50% comparado con no emplearlo (24). Considerando la alta disponibilidad del toldillo en la población urbana de Quibdó, podría considerarse la implementación de campañas de impregnación de toldillos.…”
Section: Discussionunclassified
“…Alexander et al 20 em um estudo de casos e controles e aplicando um modelo multivariado, mostraram que o uso de mosquiteiros impregnados esteve associado a uma redução de 56% dos casos de malária quando comparados com a população que não usou estas tecnologias. Esse resultado é similar ao encontrado na revisão de Lengeler 21 , em que foi encontrado um valor de 48% de eficácia.…”
Section: Os Sistemas De Vigilância E Controle Da Malária Na Fronteiraunclassified